Radiation therapists' and radiation oncology medical physicists' perceptions of work and the working environment in Australia: a qualitative study. (5th May 2016) - Halkett, G.K.B.; McKay, J.; Hegney, D.G.; Breen, Lauren J.; Berg, M.; Ebert, M.A.; Davis, M.; Kearvell, R.
Abstract : Workforce recruitment and retention are issues in radiation oncology. The working environment is likely to have an impact on retention; however, there is a lack of research in this area. The objectives of this study were to: investigate radiation therapists' (RTs) and radiation oncology medical physicists' (ROMPs) perceptions of work and the working environment; and determine the factors that influence the ability of RTs and ROMPs to undertake their work and how these factors affect recruitment and retention. Semi‐structured interviews were conducted and thematic analysis was used. Twenty‐eight RTs and 21 ROMPs participated. The overarching themes were delivering care, support in work, working conditions and lifestyle. The overarching themes were mostly consistent across both groups; however, the exemplars reflected the different roles and perspectives of RTs and ROMPs. Participants described the importance they placed on treating patients and improving their lives. Working conditions were sometimes difficult with participants reporting pressure at work, large workloads and longer hours and overtime. Insufficient staff numbers impacted on the effectiveness of staff, the working environment and intentions to stay. Staff satisfaction is likely to be improved if changes are made to the working environment. We make recommendations that may assist departments to support RTs and ROMPs.